Neurosurgical Admission Later Than 4 h After the Emergency Call Does Not Result in Worse Long-Term Outcome in Subarachnoid Haemorrhage - Sonne, Asger; Andersen, Jesper B.; Eskesen, Vagn; Lippert, Freddy; Waldorff, Frans B.; Siersma, Volkert; Lohse, Nicolai; Rasmussen, Lars S. (Frontiers in Neurology, 2021)
Abstract Background Few studies have investigated the importance of the time interval between contact to the emergency medical service and neurosurgical admission in patients with spontaneous subarachnoid haemorrhage. We hypothesised that longer time to treatment would be associated with an increased risk of death or early retirement. Methods This was a retrospective observational study with four years follow-up. Those who reached a neurosurgical department in less than four hours were compared with those who reached it in more than four hours. Individual level data were merged from the Danish National Patient Register, medical records, the Copenhagen Emergency Medical Dispatch Centre, the Civil Registration System, the Ministry of Employment and Statistics Denmark. Patients were ≥18 year and had a verified diagnosis of spontaneous subarachnoid haemorrhage. The primary outcome was death or early retirement after four years. Results Two hundred sixty-two patients admitted within a three-and-a-half-year time period were identified. Data were available in 124 patients, 61 of them were in their working age. Four-year all-cause mortality was 25.8%. No significant association was found between time to neurosurgical admission and risk of death or early retirement (OR=0.35, 95% confidence interval (CI): 0.10-1.23, p=0.10). Conclusion We did not find an association between the time from emergency telephone call to neurosurgical admission and the risk of death or early retirement.